Activated Bamboo Charcoal by ZnCl2 as Remazol Yellow FG Adsorbent: Isotherm, Kinetic, and Thermodynamic Studies - Manurung, Manuntun; Suaniti, Ni Made; Ratnayani, Oka (Chemistry Department, The University of Brawijaya, 2024)
The aim of this study was to determine the isotherm, kinetics, and thermodynamics of remazol yellow FG dye adsorption by ZnCl2-activated bamboo charcoal. The research was started by making charcoal from bamboo stems, then the quality was checked against SNI. Adsorption isotherms were tested against Langmuir and Freundlich models. The adsorption kinetics were examined against pseudo-1st and pseudo-2nd orders and thermodynamic parameters were determined by measuring the values of enthalpy (∆Ho), entropy (∆So), and free energy (∆Go). The values of ∆Ho, ∆So, and ∆Go are -29.747 KJ/mol, -93.798 J/mol, and -1.327 KJ/mol respectively. The adsorption of remazol yellow FG by activated bamboo charcoal was spontaneous. Keywords: adsorption, kinetics, chromium, bamboo charcoal, thermodynamics